Pemberdayaan Literasi Digital Berbasis Dakwah Islam Di Desa Sukamaju Kabupaten Ketapang - Haris (FIRDAUS, 2025)
The advancement of digital technology opens up great opportunities for the dissemination of Islamic da’wah. However, digital literacy among rural communities remains limited, thus requiring guidance to enable them to use digital media wisely and in line with Islamic values. This study aims to empower digital literacy based on Islamic da’wah for the residents of Sukamaju Village through training and mentoring programs involving lecturers and students. The research method employed is participatory action research, with activities including training on the use of digital media, creation of Islamic da’wah content, and guidance on digital ethics. The results show a significant improvement in participants’ ability to create and disseminate da’wah content, understand digital literacy, and develop a critical attitude toward digital information. In conclusion, the Islamic da’wah-based digital literacy empowerment program is effective in enhancing the digital competence of rural communities while instilling Islamic values in the use of technology. Keywords: Digital literacy, Islamic da’wah, Sukamaju Village, Empowerment, Training